2008
DOI: 10.1093/treephys/28.2.215
|View full text |Cite
|
Sign up to set email alerts
|

Sucrose (JrSUT1) and hexose (JrHT1 and JrHT2) transporters in walnut xylem parenchyma cells: their potential role in early events of growth resumption

Abstract: In temperate woody species, the vegetative growth period is characterized by active physiological events (e.g., bud break), which require an adequate supply of soluble sugars imported in the xylem sap stream. One-year-old shoots of walnut (Juglans regia L. cv. 'Franquette') trees, which have an acrotonic branching pattern (only apical and distal vegetative buds burst), were used to study the regulation of xylem sugar transporters in relation to bud break. At the end of April (beginning of bud break), a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
67
0
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(72 citation statements)
references
References 45 publications
3
67
0
2
Order By: Relevance
“…8.4 ). Transcript and protein levels of several of these putative transporters have been studied in walnut (Decourteix et al 2006(Decourteix et al , 2008. While the sucrose transporter JrSUT1 was strongly up-regulated in xylem parenchyma cells during bud break, two hexose transporters, JrHT1 and JrHT2, were abundant during the period of intense radial growth.…”
Section: Translocation Of Soluble Sugarsmentioning
confidence: 99%
See 1 more Smart Citation
“…8.4 ). Transcript and protein levels of several of these putative transporters have been studied in walnut (Decourteix et al 2006(Decourteix et al , 2008. While the sucrose transporter JrSUT1 was strongly up-regulated in xylem parenchyma cells during bud break, two hexose transporters, JrHT1 and JrHT2, were abundant during the period of intense radial growth.…”
Section: Translocation Of Soluble Sugarsmentioning
confidence: 99%
“…Expanding buds and the active cambial zone represent the strongest sinks during this period. Both of these tissues receive carbohydrates stored in sapwood (Hill et al 1995 ;Bonhomme et al 2010 ;Decourteix et al 2008 ). While little is known about the partitioning of reserves between these two tissues, it can be expected that it is closely related to the offset between the cambium and bud phenology.…”
Section: The Role Of Sapwood Nsc At the Whole Plant Levelmentioning
confidence: 99%
“…Experiments by Alves et al (2004Alves et al ( , 2007 found that plasma membrane H + -ATPase plays an important role in the uptake of carbohydrates from xylem vessels during growth resumption in English walnut. Sucrose and hexose transporters (JrSTU1, JrHT1, JrHT2) involved in parenchyma cells of xylem vessels were also identified in English walnut (Decourteix et al 2006(Decourteix et al , 2008.…”
Section: Acclimation To Freezing Temperatures and Embolism Recoverymentioning
confidence: 97%
“…4). Sucrose demand by developing buds, leaves, and shoots provides a sink needed to move carbohydrates into the xylem (Decourteix et al 2008;Bonhomme et al 2010). This positive xylem pressure refills vessels, which regain hydraulic function .…”
Section: Acclimation To Freezing Temperatures and Embolism Recoverymentioning
confidence: 99%
“…Contudo, as bases bioquímicas e/ou fisiológicas dos fatores causadores da acrotonia são ainda hipotéticas, pois as abordagens experimentais focadas nos gradientes são pouco desenvolvidas. Alguns estudos relativos aos gradientes de brotação abordaram as bases tróficas (Brunel, 2001;Leite, 2004;Alves et al, 2007;Decourteix et al, 2008), os hormônios (Crabbé, 1987) e o estado hídrico (Leite, 2004).…”
Section: Introductionunclassified